Paired Associative Stimulation with High-Frequency Peripheral Component Leads to Enhancement of Corticospinal Transmission at Wide Range of Interstimulus Intervals - Shulga, Anastasia; Zubareva, Aleksandra; Lioumis, Pantelis; Mäkelä, Jyrki P. (Frontiers in Human Neuroscience, 2016)
Background In spinal paired associative stimulation (PAS), orthodromic and antidromic volleys elicited by transcranial magnetic stimulation (TMS) and peripheral nerve stimulation (PNS) coincide at corticomotoneuronal synapses at the spinal cord. The interstimulus interval (ISI) between TMS and PNS determines whether PAS leads to motor-evoked potential (MEP) potentiation or depression. PAS applied as a long-term treatment for neurological patients might alter conduction of neural fibers over time. Moreover, measurements of motoneuron conductance for determination of ISIs may be challenging in these patients. Results We sought to design a PAS protocol to induce MEP potentiation at wide range of ISIs. We tested PAS consisting of high-intensity (100% SO) TMS and high-frequency (50 Hz) PNS in 5 subjects at 5 different ISIs. Our protocol induced potentiation of MEP amplitudes in all subjects at all tested intervals. TMS and PNS alone did not result in MEP potentiation. The variant of PAS protocol described here does not require exact adjustment of ISIs in order to achieve effective potentiation of MEPs. Conclusions This variant of PAS might be feasible as a long-term treatment in rehabilitation of neurological patients.